Middle to Late Holocene Variations in Salinity and Primary Productivity in the Central Baltic Sea: A Multiproxy Study From the Landsort Deep - van Wirdum, Falkje; Andrén, Elinor; Wienholz, Denise; Kotthoff, Ulrich; Moros, Matthias; Fanget, Anne-Sophie; Seidenkrantz, Marit-Solveig; Andrén, Thomas (Frontiers in Marine Science, 2019)
Anthropogenic forcing has led to an increased extent of hypoxic bottom areas in the Baltic Sea during recent decades. The Baltic Sea ecosystem is naturally prone to the development of hypoxic conditions due to its geographical, hydrographical, geological, and climate features. Besides the current spreading of hypoxia, the Baltic Sea has experienced two extensive periods of hypoxic conditions during the Holocene, caused by changing climate conditions during the Holocene Thermal Maximum (HTM; 8-4.8 cal ka BP) and the Medieval Climate Anomaly (MCA; 1-0.7 cal ka BP). We studied the variations in surface and bottom water salinity and primary productivity and their relative importance for the development and termination of hypoxia by using microfossil and geochemical data from a sediment core retrieved from the Landsort Deep during IODP Expedition 347 (Site M0063). Our findings demonstrate that increased salinity was of major importance for the development of hypoxic conditions during the HTM. In contrast, we could not clearly relate the termination of this hypoxic period to salinity changes. The reconstructed high primary productivity associated with the hypoxic period during the MCA is not accompanied by considerable increases in salinity. Our proxies for salinity show a decreasing trend before, during and after the MCA. Therefore, we suggest that this period of hypoxia is primarily driven by increasing temperatures due to the warmer climate. These results highlight the importance of natural climate driven changes in salinity and primary productivity for the development of hypoxia during a warming climate.